The Information Seeking Strategies of Digitized Resources in Cebu Technological University, Philippines - Ve Leslie E. Atanoza; Johannes M. Camasura (Philippine Association of Institutions for Research, Inc., 2012)
The study investigates the strategies employed by the students of Cebu Technological University in searching information using digitized resources. It identifies students' information needs using the main campus' library and describes the information seeking approaches students employ using the Internet, Online databases and Optical media. The study employs simple purposive sampling. It uses descriptive method of survey and document analysis. A focus group discussion was also conducted and computer log monitoring analysis. The study revealed that students' information needs are varied and course related. Students' purposes in searching information in digitize sources are to get an overview of their research topic; answering class assignments and gathering related literature. Students supply their own keywords rather than the keywords provided in the index of online databases was generally the first approach used in searching information in digitized sources. Boolean operators and truncations as search techniques were the least used approach. Search engines of Google, Yahoo, and You Tube were the top three preferences of students when using the Internet as a Digitized Information Source. Dealing with too many results to choose from and inadequate instructions on how to proceed with the search usually contribute to the delay in finding the needed information.